Pengaruh Iklan dan Promosi Penjualan di Televisi terhadap Brand Awareness Bukalapak pada Pengunjung Kota Padangsidimpuan - Hardana, Ali; Lubis, Aswadi; Isa, Muhammad (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Indonesia's market industry is the most competitive in Southeast Asia. This is evidenced by the large number of markets in Indonesia, which accept both foreign and domestic products. Market companies use various marketing strategies to increase public brand awareness. One of them is marketing through television media. Advertising content (X1) and sales promotion programs (X2) are offered and demonstrated as strategies to grow brand knowledge (Y) in the minds of potential customers. Bukalapak uses TV commercials to market. From 2021 to 2023, Bukalapak spent more money on advertising than all other online stores